Autotrophic and heterotrophic soil respiration responds asymmetrically to drought in a subtropical forest in the Southeast China. (August 2018) - Huang, Shide; Ye, Gongfu; Lin, Jie; Chen, Kaituan; Xu, Xia; Ruan, Honghua; Tan, Fanglin; Chen, Han Y.H.
Abstract: Both increasing frequency of drought and drought duration are expected for many terrestrial ecosystems under on-going climate change. However, our understanding of the drought effect on soil respiration ( R s ), which comprises the second largest carbon (C) flux of the global C cycle, remains limited. To explore the effects of reduced precipitation on R s and its components, we conducted an experiment of throughfall rainfall exclusion during two consecutive growing seasons in a subtropical forest in the Southeast China. Following throughfall exclusion R s declined rapidly, and did not recover until three to four months following rewetting, in both 2014 and 2015. During the experiment, throughfall exclusion significantly reduced autotrophic soil respiration ( R a ); however, heterotrophic soil respiration ( R h ) was unaffected, resulting in a reduced contribution ( R a / R s ) from 33 ± 1% for the control to 16 ± 3% under throughfall exclusion. Experimental drought significantly reduced soil microbial C and fine root biomass, and subsequent to rewetting, soil microbial C recovered quickly, but fine root biomass relapsed slowly. Our results suggested that prolonged drought decreases R s through modifications in soil microbial activities and fine root metabolic capacity, which are induced by reduced soil water availability. Moreover, our results imply that drought-induced reductions in R s originate primarily from R a . Our results highlight the need to account for asymmetric responses to drought between R a and R h when predicting the reaction of the ecosystem C balance in response to future drought events. Highlights: Prolonged drought sharply decreased R s and temperature sensitivity Q10 . The negative effects of droughts were more pronounced in R a than R h . The weak response of R s was discovered subsequent to rewetting. The reduction of drought-induced R s originated primarily from R a . The decrease in R s was related to modifications in soil microbe and fine root activities.